Neonatal Severe Hyperbilirubinemia Online Registry in Jiangsu Province: protocol for a multicentre, prospective, open, observational cohort study. Issue 2 (5th February 2021) - Li, Qianqian; Deng, Xiaoyi; Yan, Junmei; Sun, Xiaofan; Dong, Xiaoyue; Chen, Xiaohui; Han, Shuping; Huo, Jie; Yu, Zhangbin
Abstract : Introduction: Severe hyperbilirubinaemia in newborns can be easily complicated by acute bilirubin encephalopathy or even kernicterus, which could lead to neurological sequelae or death. However, there is no systematic study of the management of severe hyperbilirubinaemia in China. The Neonatal Severe Hyperbilirubinemia Online Registry study aims to investigate the management of jaundice before admission, risk factors and outcomes of severe hyperbilirubinaemia in a real-world setting in China. Methods and analysis: This is a prospective, multicentre, open, observational cohort study. From May 2020 to April 2023, more than 2000 patients with neonatal severe hyperbilirubinaemia from 13 tertiary hospitals in Jiangsu Province will join the study. Demographic data and treatment information will be collected from their clinical data. Management measures for jaundice before admission will be collected by the WeChat applet (called 'Follow-up of jaundice') after being provided by the patient's guardian using a mobile phone. Follow-up data will include cranial MRI examination results, brainstem auditory-evoked potential or automatic auditory brainstem response, physical examination results and Griffiths Development Scales-Chinese at the corrected ages of 3–6 months and 1 and 2 years. Results and conclusions will be recorded using 'Follow-up of jaundice.' In-hospital outcomes, including severity of hyperbilirubinaemia (severe, extreme, hazardous), acute bilirubin encephalopathy (mild, moderate, severe) and survival status (death or survival), will be collected at discharge. Follow-up outcomes will include loss to follow-up, survival status and kernicterus (yes or no) at 2 years. The research will enhance our comprehensive knowledge of jaundice management before admission, risk factors and outcomes of severe hyperbilirubinaemia in China, which will ultimately help to reduce the incidence of neonatal severe hyperbilirubinaemia. Ethics and dissemination: Our protocol has been approved by the Medical Ethics Committee of Nanjing Maternity and Child Health Care Hospital. We will present our findings at national conferences and peer-reviewed paediatrics journals. Trial registration number: NCT04251286 .